Xtreme sports : cutting edge - Maxwell, E. J. (New York : Scholastic Inc., 2003)
This book is about the new crop of extreme sports stars from Apolo Ohno to superstar skateboarder Shaun White to phenom climbing star Tori Allen. Each chapter focuses on a different sport and star, and is full of photos, bio info, trivia, anecdotes, quotes, and stats. The complete list of athletes in this book is as follows: climber Tori Allen, surfer Layne Beachley, snowboarder Tara Dakides, motocrosser Mike Metzger, BMXer Dave Mirra, speed skater Apolo Anton Ohno, snowboarder Ross Powers, and skateboarder Shaun White.
Introduction -- Tori Allen -- Layne Beachley -- Tara Dakides -- Mike Metzger -- Dave Mirra -- Apolo Ohno -- Ross Powers -- Shaun White.
Keywords: Extreme sports; Extreme sports; Sports; Athletes